(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Feasibilty Analysis of Business Development of A Cocoa Bean Brownies Business (Case Study of The “Orlenalycious” Business, Denpasar, Bali). This study aims to analyze the feasibility of developing a cocoa-based brownie business in Denpasar City, using a case study of the "Orlenalycious" business in Denpasar, Bali. The research methods used included analysis of marketing and market aspects, human resources, organizational management and technology, and financial aspects to assess the business’s overall prospects. The results indicate that market demand for cocoa-based brownies is quite high, supported by the trend of consuming healthy and local foods. Financial analysis indicates that this business has good business feasibility, as evidenced by the R/C Ratio and Break Event Point (BEP) indicators, which meet the feasibility criteria for such a business. From a management and operational perspective, "Orlenalycious" has an efficient organizational structure and production processes, as well as a marketing strategy that is adaptive to market developments in Denpasar City.Therefore, developing a cocoa-based brownie business in this business is deemed feasible and can contribute positively to the local economy and empower cocoa commodities in Bali.